2003
DOI: 10.1200/jco.2003.06.178
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adjuvant Chemotherapy and Radiation Therapy for Colorectal Cancer in a Population-Based Cohort

Abstract: Use of adjuvant therapy for colorectal cancer varies substantially by age, race, marital status, hospital volume, and individual hospital, indicating opportunities to improve care. With enhanced data on adjuvant therapies, population-based registries could become a valuable resource for monitoring the quality of cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
203
5
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(225 citation statements)
references
References 42 publications
13
203
5
4
Order By: Relevance
“…Consistent with other studies conducted in the United States, [3][4][5][6][7][8] age was the factor related most significantly to not receiving guideline-recommended treatment after adjusting for comorbidities, although studies have demonstrated that neither the survival advantage 6,23 nor toxicity 23 of adjuvant chemotherapy are related to age in patients with stage III colon adenocarcinoma. Large studies conducted in the United States based on Medicare patients (aged 65 years) diagnosed in the early to middle 1990s indicated that 50% 8 to 55% 5 of patients with stage III colon adenocarcinoma received adjuvant chemotherapy, whereas an estimate for patients who were diagnosed in 2002 3 was 63%.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with other studies conducted in the United States, [3][4][5][6][7][8] age was the factor related most significantly to not receiving guideline-recommended treatment after adjusting for comorbidities, although studies have demonstrated that neither the survival advantage 6,23 nor toxicity 23 of adjuvant chemotherapy are related to age in patients with stage III colon adenocarcinoma. Large studies conducted in the United States based on Medicare patients (aged 65 years) diagnosed in the early to middle 1990s indicated that 50% 8 to 55% 5 of patients with stage III colon adenocarcinoma received adjuvant chemotherapy, whereas an estimate for patients who were diagnosed in 2002 3 was 63%.…”
Section: Discussionsupporting
confidence: 82%
“…After a series of studies conducted in the United States that identified patient characteristics associated with not receiving guideline-recommended adjuvant chemotherapy in patients with stage III colon adenocarcinoma, [3][4][5][6][7][8][9] in the current study, we investigated whether similar population-based observations could be made in a similar patient cohort in Alberta. Patient characteristics that were associated with not having a consultation with an oncologist also were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] There are several explanations why elderly patients receive adjuvant chemotherapy less often than younger patients, such as the presence of comorbidities, unfavourable performance status or patient refusal. [38][39][40] Our study is hampered by the lack of information about comorbidities and performance status of the patient at time of diagnoses. Nevertheless marked differences in performance status of patients between hospitals in the Netherlands have not been reported.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…4 Regardless of the benefits and survival advantage gained by adjuvant chemotherapy, several studies have demonstrated that large proportions of patients do not receive it or experience treatment delays. [5][6][7][8][9] The objectives of the current study were 1) to quantify the proportion of patients receiving adjuvant chemotherapy within 12 weeks after surgery, 2) to identify factors associated with the receipt of timely adjuvant chemotherapy, and 3) to assess the association between the receipt and timing of initiation of adjuvant chemotherapy and survival among patients who were diagnosed with stage III colon cancer in Alberta between 2000 and 2005.…”
mentioning
confidence: 99%